EXTRACTION OF POLYPHENOL FROM Sargassum sp. AND ITS ENTRAPMENT IN THE NANOCHITOSAN - Wikanta, Thamrin; ', Baihakki; ', Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Seaweed is substantial in bioactive compounds of polyphenols that can scavengefree radicals. The aim of this study was to determine the total content of polyphenoliccompounds in the Sargassum sp and its aktivities by using DPPH and FRAP methods.DPPH methods resulting the value of IC50 (Inhibition concentration) and FRAPmethods resulting the total of Fe3+ reduced to Fe2+. Entrapment of Sargassum sp. extractusing nanoparticle chitosan-based was to protect the active compounds in the extract tokeep well the activity of the polyphenol of extraction. Results showed that totalpolyphenol contents of Sargassum polycistum and S. hystrix at 10 mg/ml were 108,64μg/mL and 65,5 μg/mL respectively. IC50 value on DPPH test of S. polycistum and S.hystrix were 667,234 μg/mL and 2861,49 μg/mL, respectively. The reasults of FRAPtest of S. polycistum extracts at concentrations of 100, 500, and 1000 μg/mL were 67,00;127,14; and 214,59 μmol/μg, respectively, while the S. hystrix extract was 48,47; 62,48;80,22μmol/μg extract. Loading capacity of chitosan-STPP and chitosan-carrageenan onpolyphenol were 0,45 and 0,34%, respectively, and entrapment efficiency of Chitosan-STPP and Chitosan-carrageenan were 21,96% and 39,62%, respectively.Keywords: Polyphenol, Sargassum sp, antioxidant , and nanochitosan